Daños de Botrytis cinérea en el cultivo de pepinillo (Cucumis sativus L.), en la comunidad de Pusír Grande, provincia del Carchi - Salazar Aguas, Luis Enrique Célimo (2019)
SUMMARY The present investigation was carried out in the community of Pusír Grande, parish of San Vicente de Pusír, whose theme was: Damage caused by gray rot (Botrytis cinerea P.), in the cultivation of cucumber (Cucumis sativus L.), the objectives were: Determine the characteristics of the pathogen (Botrytis cinerea) that attacks the crop; Identify the damages caused by the pathogen and the transmission vectors of the disease; To know the management carried out by the producers for the control of the disease in the cultivation of the gherkin (Cucumis sativus). Gherkin cultivation is attacked by several diseases that cause damage and even the death of plants, it is therefore very important to identify this group of diseases in order to make appropriate decisions to prevent and in cases of attack to fight diseases, mainly the gray rot (Botrytis cinerea) which is the most important due to its incidence and severity. From the information obtained in the field it was determined that 60% of the producers sow this crop between 1 to 2 ha and 40% sow less to 1 ha; Gherkin production in the area reaches an average of 1250 bags / ha, whose profitability on average is 1530 USD / ha; in the area, producers have identified seven diseases, which cause great damage to the gherkin cultivation, in some cases they have the same causal agent, but with a different vulgar name; the only method of control is the application of chemical products, which depending on weather conditions farmers apply every eight days, if the conditions are of high humidity the frequency of application is less, but if this humidity falls in its levels, the application can do it at higher frequencies; The doses of chemical products, depending on the active ingredients range from 100 to 500 grams. Keywords: pickle, pathogen, Botrytis, Control method,